The Implementation Of Outdoor Study Method In Improving Students Critical Thinking Skills In Social Study - Syahril, Agam Muhamad (International Journal Pedagogy of Social Studies, 2017)
The background of this research was defined based on the issue that the researcher found in the process of social study which showed students with low critical thinking skills. The research aims to address the problem through the implementation of the outdoor study. The implementation of outdoor study was believed could be a proper learning method in developing students’ critical thinking. The method used in this study was classroom action research. Indicators of critical thinking listed in this study were give simple descriptions with sub indicators of identifying or formulating questions, identifying the answers, arguments, and opinion by using their own ideas, commenting on the problem and appreciating others’ opinion. Analyzing by using sub indicators of comprehending the findings, connected the findings with the materials, and identifying the problems. The conclusion was established by using sub indicators of giving solution to the existed problems, giving the conclusion based on the materials and the problem emerged during the research. According to the findings, it was denoted that all aspects of the critical thinking indicators were successfully done. It could be seen from the improvement showed by the students in every cycle through the implementation of outdoor study. The connection between outdoor study and the improvement of students’ critical thinking skills was the implementation of outdoor study method introduced the students to the contexts whilst in usual, students only learn through the books, so the outdoor study makes the learning more contextual and meaningful. Also, it could train students’ critical thinking. The general conclusion was the implementation of outdoor study method could improve students’ critical thinking skills in social study at class 8J in SMPN 4 Cimahi.